Correlation between inflation rate and employment with gross demostic product / Alias Teh Sofia - Alias, Teh Sofia (Faculty of Business and Management, 2010)
This paper attempts to study the correlation exist between inflation rate and employment with gross domestic product. The variables were selected based on relevant economic theories that allow for the interaction among inflation rate and total employment in addition to response to gross domestic product. In order to achieve this objective, the Vector Error Corrected Model (VECM) is employed to determine the relationship between the variables selected in the long run. As a result, the researcher found that inflation rate is not affect the gross domestic product in the long run but employment has negative relation with gross domestic product. Besides that, Granger Causality is applied to test the causality between the variables. The findings revealed that both of independent variables have uni- directional with gross domestic product in the short run.